Urgensi Dakwah Media Cyber Berbasis Peace Journalism - Khoiruzzaman, Wahyu (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2016)
Phenomenon of media use as a means of preaching is now growing and growing along with the development of communication technology, especially the internet presence (based online). The number of media propaganda based online not all be good news because of which it displays scary face in the terror shape, threats and provocation. Views such inconsistent with the principles of Islam as a religion of peace and uphold peace. Preacher on media propaganda based online should perform work activities are guided by the values and teachings of Islam, as well as being the peacemaker. Considering its importance, it is necessary to know the journalists propaganda and apply the principles of peace journalism as a complement in carrying out the duties of journalism. Promoting peace through peace journalism perspective more useful in view of a phenomenon or event, in particular the events of the conflict.***Fenomena penggunaan media sebagai sarana untuk berdakwah kini semakin bertambah dan berkembang seiring dengan perkembangan teknologi komunikasi, khususnya dengan keberadaan internet (berbasis online). Banyaknya media dakwah berbasis online tidak seluruhnya menjadi kabar gembira lantaran diantaranya justru menampilkan wajah yang menakutkan dalam bentuk teror, ancaman dan provokasi. Tampilan semacam itu bertolak belakang dengan prinsip agama Islam sebagai agama damai dan menjunjung tinggi perdamaian. Da’i pada media dakwah online semestinya melakukan aktifitas kerja yang berpedoman pada nilai-nilai dan ajaran agama Islam, serta menjadi juru damai. Mengingat pentingnya hal tersebut, dirasa perlu bagi para jurnalis dakwah untuk mengetahui dan menerapkan prinsip jurnalisme damai sebagai pelengkap dalam melaksanakan tugas-tugas jurnalistik. Jurnalisme damai mengedepankan perdamaian melalui sudut pandang yang lebih bermanfaat dalam melihat suatu fenomena atau peristiwa, khususnya peristiwa konflik.